2014
DOI: 10.1007/s10620-014-3319-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Helicobacter pylori Genotypes with Gastric Histopathology in the Central Region of a South-European Country

Abstract: Background Outcome of Helicobacter pylori (H. pylori) infection results from interaction of multiple variables including host, environmental and bacterial-associated virulence factors. Aim This study aimed to investigate the correlation of cagA, cagE, vacA, iceA and babA2 genotypes with gastric histopathology and disease phenotype in the central region of a South-European country. Methods This prospective study involved 148 infected patients (110 female; mean age 43.5 ± 13.4 years) submitted to endoscopy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 57 publications
(95 reference statements)
1
10
1
Order By: Relevance
“…Several studies suggest that the evolution of gastric lesions is related to the genetic diversity of H. pylori. 4,35,36 This data do not support results of studies conducted in Portugal, 4 in Italy, 5 in Netherlands, 37 in Greece 7 and in Colombia 38 who report a significant association between vacAs1 and neutrophilic activ- With regard to toxic habits, only tobacco consumption was found to be a risk factor of neutrophilic activity that confirms our preliminary results 9 and is supported by a functional study that revealed a significant association between the mRNA expression of epithelial neutrophil-activating protein 78 and smoking. 39 However, other studies reported that smoking status was a significant predictor for intestinal metaplasia and dysplasia 40,41 and is associated with glandular atrophy.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies suggest that the evolution of gastric lesions is related to the genetic diversity of H. pylori. 4,35,36 This data do not support results of studies conducted in Portugal, 4 in Italy, 5 in Netherlands, 37 in Greece 7 and in Colombia 38 who report a significant association between vacAs1 and neutrophilic activ- With regard to toxic habits, only tobacco consumption was found to be a risk factor of neutrophilic activity that confirms our preliminary results 9 and is supported by a functional study that revealed a significant association between the mRNA expression of epithelial neutrophil-activating protein 78 and smoking. 39 However, other studies reported that smoking status was a significant predictor for intestinal metaplasia and dysplasia 40,41 and is associated with glandular atrophy.…”
Section: Resultsmentioning
confidence: 99%
“…6 We found a significant association between cagA-positive strains and severity of the disease: 35.3% vs 81.8% in the mild-and severe-disease group, respectively. 30 Infection experiments showed that 22.2% cagA-positive strains were unable to translocate CagA into the host cells, showing non-expression of cagA or a non-functionality of the cag-T4SS of these strains. [4][5][6] Other study, conducted in South of Spain in patients with milddisease symptom, reported a prevalence of 37.3% of cagApositive and 18.6% cagA/vacAs1m1, 25 and similar data were reported in Portugal in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Other study, conducted in South of Spain in patients with milddisease symptom, reported a prevalence of 37.3% of cagApositive and 18.6% cagA/vacAs1m1, 25 and similar data were reported in Portugal in 2015. 30 Infection experiments showed that 22.2% cagA-positive strains were unable to translocate CagA into the host cells, showing non-expression of cagA or a non-functionality of the cag-T4SS of these strains. The babA gene holds two different alleles, only the babA2 encodes the functional BabA and the formation of chimera between babA2 and the homologous babB and babC genes regulates protein expression on transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Urea breath test, fecal antigen test and serology are among those non-invasive methods [15]. PCR method has a higher sensitivity and specificity which can cover many other queries such as needing to rapid and non-invasive diagnosis, determination of mutations related to the antibiotic resistance alongside virulence factors encoding genes, and genotyping [16][17][18].…”
Section: Discussionmentioning
confidence: 99%